Apakah Self Efficacy Memediasi Pengaruh Kompetensi, Mindset, Pendidikan terhadap Kesempatan Kerja Lulusan Fakultas Ekonomi dan Bisnis Universitas PGRI Semarang ? - Yahya, Rifan; Utami, Ratih Hesti; Setiawati, Ira (STIE Widya Manggala, 2023)
The research was conducted aiming to determine the effect of mindset competency, education through self-efficacy as a mediating variable on job opportunities for graduates of the Faculty of Economics and Business, PGRI University Semarang. The research method used is quantitative descriptive analysis. The population of this study used a saturated sample, meaning that the entire population consisted of 118 graduates. Data obtained through the telegram group